1992
DOI: 10.4315/0362-028x-55.7.534
|View full text |Cite
|
Sign up to set email alerts
|

Hazards and Critical Control Points of Vending Operations at a Railway Station and a Bus Station in Pakistan

Abstract: Hazard analyses (which included watching operations, measuring temperatures of foods throughout preparation and display, and sampling and testing for microorganisms of concern) were conducted of vending operations at a railway and a bus station in a large city in Pakistan. Commonly prepared foods which were surveyed included: rice, pulses, chick peas, ground meat and potato mixtures, meat stew, and okra. Temperatures were measured and samples were collected from a variety of other foods. Large numbers (104–7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 0 publications
1
25
0
2
Order By: Relevance
“…Foods were exposed to flies and this could result to epidemiological disease outbreak like cholera (Ashenafi, 2009). Foods that were stored in container/cupboard other than refrigerator are likely to be contamination by pathogenic micro-organisms and associated with reduced quality (WHO, 1984;Bryan et al, 1992;Mensah et al, 2002). The oily appearance of water used for washing the crockery confirms the wash water reuse practice amongst the vendors surveyed.…”
Section: Waste Disposal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foods were exposed to flies and this could result to epidemiological disease outbreak like cholera (Ashenafi, 2009). Foods that were stored in container/cupboard other than refrigerator are likely to be contamination by pathogenic micro-organisms and associated with reduced quality (WHO, 1984;Bryan et al, 1992;Mensah et al, 2002). The oily appearance of water used for washing the crockery confirms the wash water reuse practice amongst the vendors surveyed.…”
Section: Waste Disposal Methodsmentioning
confidence: 99%
“…In developing countries especially Nigeria, there is a noticeable increase in the number of street food vendors as a result of dwindling economy and unemployment. According to WHO (1984), Bryan et al (1992) and Ashenafi (1995), food exposed for sale on the streets may become contaminated either by spoilage or pathogenic micro-organisms. Furthermore, it is also reported that street-vended foods have epidemiological links with illness (El-Sherbeeny et al, 1985;Abdulsalam and Kaferstein, 1993;Muinde and Kuria, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the total coliform count were ranging from 3 to 1400 MPN per 100 ml. The MacConkey's agar count ranged from 2× 10 2 to 2.7×10 4 , and mannitol salt agar count ranged from 2× 10 2 to 1.6×10 4 per ml (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Microbiological quality investigations of street-vended foods have reported high bacterial counts and a high incidence of food borne pathogens in such foods in different countries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Na maioria das vezes, casos de infecções alimentares estão relacionadas ao consumo de alimentos que sofrem manipulação exacerbada associada as más condições de armazenamento e acondicionamento, permitindo a exposição direta ao ambiente, propiciando a contaminação e posterior veiculação de agentes de natureza infecciosa aos consumidores [3,4,5,6,18,26]. Os microrganismos representam uma ameaça à segurança dos alimentos, podendo ser causadores de doenças de origem alimentar.…”
Section: -Introduçãounclassified